VIRTUAL EDUCATION BASED UPON INFORMATION TECHNOLOGIES - Eyzaguirre Tejada, Roberto (2004)
This article presents a virtual education module for the Faculty of Industrial Engineering. Some tools such as MySQL, PHP, Apache, HTML y Moodle were used for its making. The purpose was to set an interactive multimedia system that enriches the teaching-learning process in the Post-Graduate Unit as well as in the Center of University Extension and Social Projection (CEUPS), thus obtaining reciprocal profits for both the University and the community.